2020
DOI: 10.4103/jfmpc.jfmpc_1115_20
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent sexual behaviour and its determinants: A hospital-based study

Abstract: Aim: To know the prevalence of sexual activity, their sexual behaviour and attitude towards sex among unmarried adolescent females. Materials and Methods: It was a hospital-based prospective observational study. The study duration was 1 year. The study participants were unmarried girls between the age group of 10–19 years who gave written informed consent. In the case of a minor, consent was obtained from parents also. Pre-designed, pre-structured and pre-tested questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“… Practices among adolescents’ girls Reviewers found ten studies describing practices around teenage pregnancy among adolescent girls. Five articles revealed that adolescents used contraceptives to prevent pregnancy [ 41 45 ]. The age of first intercourse was discussed in two papers [ 32 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Practices among adolescents’ girls Reviewers found ten studies describing practices around teenage pregnancy among adolescent girls. Five articles revealed that adolescents used contraceptives to prevent pregnancy [ 41 45 ]. The age of first intercourse was discussed in two papers [ 32 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five articles revealed that adolescents used contraceptives to prevent pregnancy [ 41 45 ]. The age of first intercourse was discussed in two papers [ 32 , 41 ]. Two articles (n = 2) explained that girls experience 1st intercourse between the age of 16 and 18 years [ 41 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By 2025, India is predicted to have the highest population of teenagers in the whole world due to the country's strong adolescent population growth. Adolescent development must include sexual behavior since it affects their health, happiness, and opportunities for the future [ 2 ]. It's critical to comprehend how teenagers behave sexually in rural parts of India since they have different social and cultural contexts from metropolitan areas [ 3 ].…”
Section: Introductionmentioning
confidence: 99%